Synthesis and Spectral Studies of Some Bioactive Transition Metal Complexes of [bis-2-(4-Fluorophenyl)prop-2-enaln]ethane-1,2-diamine - Singh, Jagvir; Anuradha; Kumar, Pradeep; Mordhwaj; Kumar, Ravi (Asian Journal of Chemistry, 2019)
Co(II), Ni(II) and Cu(II) metal complexes of a novel Schiff base ligand (SBL) derived from condensation of 2-(4-fluorophenyl)prop-2-enaln and ethane-1,2-diamine were synthesized. All the complexes were characterized by elemental analyses, IR, UV-visible spectroscopy, magnetic susceptibility and conductance measurements and 1H NMR. From the elemental analysis data, 1:1 [M]:[ligand] metal chloride complexes are formed having the general composition [M(SBL)Cl2] and [Cu(SBL)] Cl2, [where M = Co(II), Ni(II) and SBL= {bis-2-(4-fluorophenyl)prop-2-enaln}ethane-1,2-diamine]. The result showed that the ligand is coordinated to the metal ions in a neutral tetradentate manner with ON donor sites and the nature of metal-ligand bonding can range from covalent to ionic. Antimicrobial activities of the newly synthesized chemical compounds were evaluated against Staphylococcus aureus (ATCC 25923), Staphylococcus aureus (ATCC 3160), Cabdida albicans (ATCC 227) and Staphylococcus cereviscae (ATCC 361) species and found that metal complexes exhibited more antimicrobial properties so they are more potential and significant than the ligand.